The Color Purple - Steven Spielberg; Busia, Akosua; Desreta Jackson; Margaret Avery; Oprah Winfrey; Whoopi Goldberg; Willard E Pugh; Danny Glover (USA Amblin Entertainment, 1985)
This film follows the life of Celie, a young black girl growing up in the early 1900's. The first time we see Celie, she is 14 - and pregnant - by her father. We stay with her for the next 30 years of her tough life...
The life and trials of a young African American Woman.
Alice Walker
Language(s): English
Subtitle(s): English, Turkish
Keywords: Musical; Drama